مساهمة النظام المحاسبي المالي في تفعيل حوكمة الشركات - مغطيط, أحمد رامي (My University, 2024)
The study aimed to estimate the extent to which Algerian institutions apply the financial accounting system and its ability to generate high-quality information that contributes to activating corporate governance and to study the extent to which Algerian institutions apply corporate governance. The descriptive approach was relied upon. In the theoretical aspect, various available sources and references were relied upon, such as books, notes and theses. In the practical aspect, a field study was conducted in order to collect information by means of the questionnaire that was designated for that. The study concluded that the financial accounting system provides an effective framework for corporate governance and ensures adequate protection for stakeholders. It also achieves justice among all shareholders, as well as guarantees the rights of shareholders.
دراسة ميدانية في مؤسسة ميناء مستغانم
Keywords: financial accounting system, corporate governance